Synergistic effect of polymer and graphene oxide nanocomposite in heterogeneous layered porous media: a pore-scale EOR Study - M. Iravani; M. Simjoo; A. H. Molaei (Journal of Petroleum Exploration and Production Technology)
Abstract Graphene oxide (GO) nanocomposites offer a novel method for enhancing oil recovery, leveraging their unique properties to improve recovery efficiency. This study investigates the potential of GO and polymer nanocomposites (GOPN) for enhanced oil recovery (EOR) in stratified and heterogeneous reservoirs. A series of glass micro-model experiments was conducted at ambient conditions to evaluate the performance of different injection scenarios. The findings demonstrated that incorporating GO nanosheets into water flooding, even at low concentration (100 ppm), increased oil recovery by 3% compared to conventional water flooding. This improvement was attributed to GO nanosheet adsorption onto grain surfaces. Furthermore, increasing the GO concentration to 500 ppm led to an additional 8% oil recovery, potentially due to enhanced sweep efficiency and better passage through pore throats. Polymer flooding achieved a significant oil recovery of 77%, and GOPN injection yielded an even higher recovery, reaching almost 87%. This 10% increase suggests a synergistic effect between the polymer and GO nanosheets. Additionally, GOPN’s ability to alter wettability towards a more water-wet state contributed to improve oil detachment and more oil recovery, a critical factor in optimizing EOR techniques. These findings highlight the potential of GOPN as a promising EOR technique in stratified reservoirs. Compared to previous studies, this work explored the performance of GOPN at low GO concentrations (100 ppm). It demonstrated a significant improvement in oil recovery (as much as 10%) compared to polymer flooding alone, paving the way for further research on GOPN for EOR applications and more efficient oil production.